(untitled) (Research, Society and Development, 2022)
Introduction: A drug is defined as any substance, natural or synthetic, which, once introduced into the living organism, can modify one or more of its functions. Their abusive use is considered a worldwide disorder, both because of the damage caused by high consumption, as well as because of the frequency with which they are used. They affect the psychological, emotional, cognitive and social aspects of adolescents, a biopsychosocial stage that is sometimes experienced in a complex and contradictory way. Objective: In this way, the present research aims to present the risk and protection factors against the abusive use of licit and illicit drugs, highlighting their causes and consequences. Methodology: This is a systematic literature review study, where the initial search via the Virtual Health Library (VHL) resulted in 546 results, using 29 articles for this review. Results and Discussion: Psychotropic drugs act directly on the CNS and can stimulate brain activities or reduce them. They can be of the hallucinogenic, stimulant or depressant type, where it is usually indicated for medical purposes, for example to alleviate pain or psychiatric treatment, when they are administered correctly the result becomes beneficial to the patient, since not all of them generate dependence. Final Considerations: In addition to the fact that chemical dependency is a public health problem, since it can affect anyone, regardless of socioeconomic class, age, gender and cultural values, it can have consequences that can reach an irreparable level, affecting the user’s entire life and even to death.